Handbook of silicon photonics - Vivien, Laurent (Boca Raton : CRC Press, 2013)
'Edited by a leader in the field, this book describes silicon photonics from the basics to integrated systems and applications. It covers a broad spectrum from the theory to applications, emphasizing passive and active photonic devices, fabrication, integration and the convergence with CMOS technology. The book includes contributions from other leading players to provide the first handbook on the subject, and at a time when the field is mature enough to warrant a single volume providing a complete overview of theory, applications, systems, and technology'--
Includes bibliographical references and index.
Keywords: Optoelectronic devices -- Handbooks, manuals, etc; Silicon -- Optical properties -- Handbooks, manuals, etc; Photonics -- Handbooks, manuals, etc